Audit Office Labor Market Proximity and Audit Quality - Lee, Gladys; Naiker, Vic; Stewart, Christopher R. (The Accounting Review, 2022)
ABSTRACT This study examines whether the audit quality of Big 4 audit firms is affected by an audit office's proximity to more target universities for appointing staff auditors. We identify these target universities using a recruitment map of a Big 4 audit firm and unique office-level hiring data hand-collected from LinkedIn. Our findings suggest that audit offices closer to more of their key feeder schools and universities with accredited business schools are associated with higher audit quality, as observed by a lower likelihood of financial accounting misstatements. Our results are robust across alternative measures of labor market proximity and audit quality, and to a battery of sensitivity tests, including controlling for client firms' proximity to universities. Overall, our results suggest that audit offices benefit from being proximate to more key suppliers of staff auditors. JEL Classifications: M42; J21.